2023
DOI: 10.1186/s13104-023-06495-9
|View full text |Cite
|
Sign up to set email alerts
|

The first ITS2 sequence data set of eDNA from honey of Malaysian giant honeybees (Apis dorsata) and stingless bees (Heterotrigona itama) reveals plant species diversity

Nurul Huda,
Saeed ullah,
Roswanira Abdul Wahab
et al.

Abstract: Objectives Pollen is a useful tool for identifying the provenance and complex ecosystems surrounding honey production in Malaysian forests. As native key pollinators in Malaysia, Apis dorsata and Heterotrigona itama forage on various plant/pollen species to collect honey. This study aims to generate a dataset that uncovers the presence of these plant/pollen species and their relative abundance in the honey of A. dorsata and H. itama. The information gathered from this study can be used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The honey produced by A . cerana and H. itama in the present study was juxtaposed with that produced by A. dorsata and H. itama [ 30 ]. This comparison conclusively revealed that all plant species contributing to the honey were indigenous to Peninsular Malaysia, with a particular emphasis on the East Coast region of Terengganu, Malaysia.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The honey produced by A . cerana and H. itama in the present study was juxtaposed with that produced by A. dorsata and H. itama [ 30 ]. This comparison conclusively revealed that all plant species contributing to the honey were indigenous to Peninsular Malaysia, with a particular emphasis on the East Coast region of Terengganu, Malaysia.…”
Section: Discussionsupporting
confidence: 53%
“… Comparison of pollen composition at the genus level between honey samples from Malaysia [ 30 ] and Karangasem, Bali, Indonesia (present study). Each represents particular pollen genus in the honey samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation